Malakas na Barangay, Malakas na Bayan: Empowering Local Leaders Through Multi-Sectoral Collaboration - Teodulo R. Cruz (Future Science / FSH-PH Publications, 2026)
The barangay, which literally means village or community, is the smallest political unit in the Philippine political structure as defined in the Local Government Code. It is led by barangay officials, who are often elected based on popularity or familial ties rather than formal credentials. These officials serve as frontliners in providing basic services and performing executive, legislative, and quasi-judicial functions. This study was conducted to strengthen the capacity of the barangay to fulfill its mandate to alleviate poverty and promote sustainable and inclusive human growth through collaboration with selected government agencies, private institutions, the academe, and community members. Using the focus group discussion, information was gathered and used to design appropriate interventions. The study yielded both positive and negative outcomes that future advocates may utilize to effect change and empower barangays in promoting sustainable human growth and development.